2016
DOI: 10.1111/jfpp.12794
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Changes of Connective Tissue Proteins in Jumbo Squid (Dosidicus gigas) Muscle During Ice Storage

Abstract: Connective tissue (CT) proteins in jumbo squid (Dosidicus gigas) play an important role because they are the responsible for the union between various cells; hence, there is a close relationship between their functions and muscle firmness during ice storage. In this study, the thermal resistance and solubility of the CT extracted from the fins, mantle and arms of jumbo squid during ice storage (20 days) was evaluated. The CT was fractionated based on solubility [NaCl‐soluble (SSCT) and insoluble (ICT)]. The so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 37 publications
2
27
0
Order By: Relevance
“…Therefore, in each anatomical region, the myofibrils (mainly composed by myosin and actin) and contractile connective proteins (such as collagen and elastin) have different supra‐organizational rearrangements. Fins and arms contain a major proportion of collagen than mantle (Osuna‐Amarillas et al, ; Torres‐Arreola, Pacheco‐Aguilar, Sotelo‐Mundo, Rouzaud‐Sández, & Esquerra‐Brauer, ), in which this connective protein serves as scaffold of actomyosin complexes, and also surely was contributed to prevent hydrolysis and loss of squid muscle proteins throughout cooking process.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, in each anatomical region, the myofibrils (mainly composed by myosin and actin) and contractile connective proteins (such as collagen and elastin) have different supra‐organizational rearrangements. Fins and arms contain a major proportion of collagen than mantle (Osuna‐Amarillas et al, ; Torres‐Arreola, Pacheco‐Aguilar, Sotelo‐Mundo, Rouzaud‐Sández, & Esquerra‐Brauer, ), in which this connective protein serves as scaffold of actomyosin complexes, and also surely was contributed to prevent hydrolysis and loss of squid muscle proteins throughout cooking process.…”
Section: Resultsmentioning
confidence: 99%
“…Torres‐Arreola et al () reported major amount of connective tissue (collagenous proteins) in muscle from fins and arms than in mantle. Besides, it has been reported that crosslinking degree of collagen in jumbo squid muscle plays an important role during post‐catch management (Osuna‐Amarillas et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Octopus displayed the highest IC content, followed by guitarfish and, finally, cazon with the least amount. These changes in solubility can be attributed to the crosslinking degree of the CT fibers, affecting the collagen solubility of the evaluated species (Osuna‐Amarillas et al, ; Ramírez‐Guerra, Fimbres‐Romero, et al, ). Moreover, these dissimilarities in the collagen solubility could be related to the firmness differences detected in the muscle of each organism.…”
Section: Resultsmentioning
confidence: 99%
“…Figure shows peaks around 97–205 kDa. Collagen molecule consists of three polypeptide chains (α, approximately 100 kDa) (Badii & Howell, ), which depending on the intramolecular crosslinking degree, can be extracted as β‐chain (two α‐chains linked by covalent bonds), a phenomenon related to the protein aggregation during postcapture management (Osuna‐Amarillas et al, ; Torres‐Arreola et al, ). Although, it may also depend on the evaluated species (age, size, sex, and habitat) (Ando et al, ).…”
Section: Resultsmentioning
confidence: 99%